2012
DOI: 10.1016/j.jocn.2012.01.033
|View full text |Cite
|
Sign up to set email alerts
|

Use of a micromanipulator system (NeuRobot) in endoscopic neurosurgery

Abstract: NeuRobot, a micromanipulator system with a rigid neuroendoscope and three micromanipulators, was developed for less invasive and telecontrolled neurosurgery.This system can be used to perform sophisticated surgical procedures through a small window 10 mm in diameter. The present study was performed to evaluate the feasibility of using NeuRobot in neuroendoscopy. Four different intraventricular neurosurgical procedures were performed using NeuRobot in three fixed cadaver heads: 1) fenestration of the floor of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 11 publications
0
13
0
Order By: Relevance
“…An additional advantage of the flexible endoscope is that it can be used in cases of intraventricular brain tumors for patients who have small ventricles, M A N U S C R I P T A C C E P T E D ACCEPTED MANUSCRIPT 6 such as in pediatric populations, for whom contemporary rigid endoscopes may not be safely deployed (13). Furthermore, while the cost of the device is likely to be higher than that of rigid rod-lens endoscopes, the flexible HD endoscope, which is fully sterilizable, could offer a more affordable and practical option for intraventricular procedures compared to comprehensive surgical systems that rely on extensive technological development with significant overhead cost (5,19).…”
Section: Beyond Improved Intraoperative Visualization and Precision mentioning
confidence: 99%
“…An additional advantage of the flexible endoscope is that it can be used in cases of intraventricular brain tumors for patients who have small ventricles, M A N U S C R I P T A C C E P T E D ACCEPTED MANUSCRIPT 6 such as in pediatric populations, for whom contemporary rigid endoscopes may not be safely deployed (13). Furthermore, while the cost of the device is likely to be higher than that of rigid rod-lens endoscopes, the flexible HD endoscope, which is fully sterilizable, could offer a more affordable and practical option for intraventricular procedures compared to comprehensive surgical systems that rely on extensive technological development with significant overhead cost (5,19).…”
Section: Beyond Improved Intraoperative Visualization and Precision mentioning
confidence: 99%
“…A system (NeuRobot, Shinshu University School of Medicine and Hitachi Ltd., Tsuchiura, Japan) using three micromanipulators is also available for ETV. 16 Balancing should be performed on the anteroposterior along with the side movement of the endoscope to check the proper orientation of the camera. It is important to be aware that the camera can rotate during the procedure and may disorient the surgeon.…”
Section: Surgical Proceduresmentioning
confidence: 99%
“…At the end of their study, authors proved that the proposed system has sufficient constraints to be effective in brain surgery. Hongo et al proposed a micromanipulator system (NeuRobot) for neurosurgery that includes three micromanipulators and an endoscope that are housed on a cylindrical component. Similar to the other mentioned systems, six degrees of freedom serial manipulator is responsible for the positioning of the system during operation.…”
Section: Introductionmentioning
confidence: 99%
“…The proposed system can be inserted into the target area from an incision of 10‐mm diameter to perform precise neurosurgical operations. In their latter work, authors simulated four different types of operations including biopsy in three cadaver heads by utilizing the proposed system. The results of their work indicated that the designed system is capable of performing sophisticated operations due to its sufficient dexterity and stability …”
Section: Introductionmentioning
confidence: 99%